2001
DOI: 10.1159/000046317
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Renal Transplantation on Pulmonary Function

Abstract: In patients with chronic renal failure, mechanical and hemodynamic changes could occur in the lungs without obvious pulmonary symptoms and findings and their effects could pave the way to pulmonary functional disorders. In this study, pulmonary functional disorders and especially alveolocapillary defects, which are frequently seen in uremia, were determined in renal transplanted patients. Pulmonary functions and diffusion capacity were assessed in uremic patients (n = 20) and in successfully transplanted patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 16 publications
3
24
0
3
Order By: Relevance
“…However, the present authors propose that the main disorders associated with these results are the following: chronic and often subclinical pulmonary edema; decreased serum albumin with consequent water and protein imbalance in the microcirculation; interstitial fibrosis and calcification of the lung parenchyma and bronchial tree; recurrent infections; and alveolitis and fibrosis due to corticosteroid therapy in immunosuppressed patients. Studies that evaluate lung function in patients with CKF undergoing dialysis and after kidney transplantation have described results similar to those found in the present study and help to explain the lesion mechanisms 14,[31][32][33] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the present authors propose that the main disorders associated with these results are the following: chronic and often subclinical pulmonary edema; decreased serum albumin with consequent water and protein imbalance in the microcirculation; interstitial fibrosis and calcification of the lung parenchyma and bronchial tree; recurrent infections; and alveolitis and fibrosis due to corticosteroid therapy in immunosuppressed patients. Studies that evaluate lung function in patients with CKF undergoing dialysis and after kidney transplantation have described results similar to those found in the present study and help to explain the lesion mechanisms 14,[31][32][33] .…”
Section: Discussionsupporting
confidence: 86%
“…In analyzing the values of total traveled distance in each group, it was observed that in the DG, only three individuals (15.63%) walked more than 500 meters, whereas 56.67% of the CG walked more than 500 meters (which is the expected minimum normal value, according to authors who mention this test) 31 . These results did not show significant associations in the chi-square test, but there was a tendency for individuals with CKF to walk shorter distances than would be expected for the general population.…”
Section: Resultsmentioning
confidence: 90%
“…27 The patients were instructed to interrupt the exercises in the presence of both "hypertension" or "hypotension" above the initial status (<200/110 mmHg or >90/70 mmHg), as well as an "SpO 2 falling" below 89%, and also in presence of the following signals and symptoms: "headache," "nape pain," "chest pain," "nausea," "vertigo," "intense muscular fatigue," "cramps," or any other debilitating muscular symptom. 28 At exercise termination, peripheral muscles' ("ischiotibial" and "triceps surae") passive elongations were developed, maintained for 20 s with two series for every limb, and finalized with passive slipping in the triceps sural muscle. 7,17 Statistical Analysis Data were analyzed with the SPSS 15.0 (Statistical Package for Social Sciences) software, version 13.0, and the quantitative variables were expressed in average and standard deviation.…”
Section: Exercise Programsmentioning
confidence: 99%
“…These findings supported the involvement of small airways detected by spirometry. Various studies reported similar results (7,(52)(53)(54). Small airway disease may be attributed to the following conditions: chronic and often subclinical pulmonary edema, decreased serum albumin with consequent water and protein imbalance in microcirculation, recurrent infections, interstitial fibrosis, and alveolitis (7,(52)(53)(54).…”
Section: Echocardiographic Datamentioning
confidence: 80%